Hydroxide-loaded noble metal particle composite catalyst, and preparation method and application thereof
By self-corroding the synthetic hydroxide-supported noble metal particles on the foam metal substrate, the problem of low activity of existing electrochemical denitrification catalysts is solved, and efficient and selective ammonia synthesis is achieved, and comprehensive energy consumption is reduced.
Patent Information
- Application Number
- CN202411792688.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-03-14
AI Technical Summary
The existing electrochemical denitrification catalysts have low activity, resulting in low selectivity of ammonia and Faraday efficiency, and Cu-based catalysts are easily toxic, have slow kinetics and high overall energy consumption.
The self-corrosion method is used to synthesize the composite catalyst of hydroxide-supported precious metal particles on the foam metal substrate to form a multi-layer structure catalyst, including the foam metal substrate, metal hydroxide nanosheet array and precious metal particles.
It improves the activity and selectivity of the catalyst, improves the Faraday efficiency and energy efficiency of the ammonia produced by electrochemical denitrification, reduces the overall energy consumption, and enhances the structural stability of the catalyst.
Smart Images

Figure CN119615256A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical wastewater denitration and clean ammonia production, and in particular to a composite catalyst of hydroxide-loaded precious metal particles and a preparation method thereof. The present invention also relates to the application of the composite catalyst in electrochemical denitration and ammonia production reactions. Background Art
[0002] Nitrogen pollution in water sources is becoming increasingly serious worldwide, and the level of nitrogen pollution has exceeded the limit that microorganisms in the water can handle. When there is sufficient oxygen in the environment, nitrogen pollutants discharged into the water body are often converted into nitrate ions (NO3 - ) form. NO3 - Concentration is an important indicator for assessing the degree of pollution in aquatic ecosystems. High concentrations of NO3 - Will destroy the aquatic ecological balance. - The main sources include nitrogen fertilizers used in agriculture, nitrogen oxides (NO x ) Acid rain from combustion, animal excrement, and NO3 - Domestic sewage and industrial wastewater. NO3 in drinking water - High concentrations may cause a variety of health problems, including cancer, liver damage and blue baby syndrome. To reduce these potential health risks, the U.S. Environmental Protection Agency (EPA) has set a limit of nitrate nitrogen (NO3 - -N) concentration is not higher than 10ppm.
[0003] In the field of industrial wastewater denitrification, biological denitrification and chemical reduction are the two main treatment technologies. Biological denitrification uses microorganisms to convert nitrates into nitrogen gas. Although this method is environmentally friendly, it is limited by its slow reaction rate and sensitivity to environmental conditions, and may produce harmful intermediates. The chemical reduction method reduces nitrates through chemical reductants. Although it can quickly reduce nitrate concentrations, it is often costly and may introduce new pollutants, posing potential risks to the environment and operators. Therefore, both methods face the problem of balancing efficiency, cost and environmental impact, and there is an urgent need to develop more efficient, economical and environmentally friendly denitrification technologies.
[0004] As an emerging technology, electrochemical denitrification has shown great potential and advantages because it can operate at room temperature and pressure, does not require additional chemical reducing agents, and can directly convert nitrates into ammonia. This method can not only effectively deal with nitrogen pollution problems, but also produce ammonia products with high economic value. By utilizing the electricity converted from renewable energy, the electrocatalytic nitrate reduction process can not only reduce dependence on traditional energy, but also reduce the energy consumption required for synthesizing ammonia, and achieve sustainable ammonia synthesis. Electrochemical denitrification technology is expected to achieve high-efficiency and high-selectivity nitrate reduction by regulating electrocatalytic materials and reaction conditions, providing a new solution for the treatment of nitrate-containing wastewater. However, electrochemical denitrification is a complex process involving multiple electrons, accompanied by competitive hydrogen evolution reactions, which limits the selectivity and Faraday efficiency of the target product ammonia; the reaction process is accompanied by the formation of intermediates with different stabilities and adsorption capacities, which leads to the diversity of reduction products and hinders the electrochemical denitrification and ammonia production process. In the prior art, the transition metal Cu has a unique outer d electron structure and has a strong interaction with the molecular orbital of the nitrate ion, so it is widely used in electrocatalytic nitrate reduction to synthesize ammonia. However, the surface of Cu-based catalysts is easily poisoned and prone to two-electron reactions to generate toxic nitrite ions, which reduces the selectivity of the ammonia synthesis reaction. In addition, the electrochemical denitrification reaction kinetics of Cu-based catalysts is relatively slow and requires a high overpotential, resulting in a high comprehensive energy consumption for ammonia production (21-38 kWh kg -1 ).
[0005] Therefore, in view of the significant demand for comprehensive treatment of industrial wastewater and clean and efficient synthesis of ammonia, the research and development of new electrocatalytic materials with high activity, high selectivity and high stability is the current research focus and difficulty. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defect of low catalyst activity in the prior art, thereby providing a method for preparing a composite catalyst of hydroxide-loaded precious metal particles, which adopts a self-corrosion method through spontaneous redox reactions to in-situ synthesize a composite structure of hydroxide-loaded precious metal particles on a metal substrate.
[0007] Furthermore, the present invention also provides the use of a composite catalyst of hydroxide-loaded precious metal particles in an electrochemical denitration and ammonia production reaction.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] A composite catalyst of hydroxide-loaded precious metal particles comprises a foam metal substrate, a metal hydroxide nanosheet array is crystallized on the surface of the foam metal substrate, and precious metal particles are attached to the surface of the metal hydroxide nanosheet array.
[0010] The foam metal substrate is foam nickel, foam cobalt or foam iron, and the metal hydroxide nanosheet arrays are respectively nickel hydroxide nanosheet arrays, cobalt hydroxide nanosheet arrays and iron hydroxide nanosheet arrays.
[0011] The noble metal particles are ruthenium, silver, palladium, gold or rhodium.
[0012] A method for preparing the composite catalyst comprises the following steps:
[0013] The pretreated foam metal substrate is immersed in a noble metal salt solution, stirred for 10 to 30 minutes, cleaned, and vacuum dried to obtain a composite catalyst of hydroxide-loaded noble metal particles.
[0014] The foam metal is selected from foam nickel, foam cobalt or foam iron.
[0015] The noble metal salt is one of ruthenium chloride, silver nitrate, palladium chloride, gold chloride or rhodium chloride, and the concentration of the noble metal salt solution is 2.5-10 mM.
[0016] The stirring speed is 400-800 rpm, the vacuum drying temperature is 50-70° C., and the vacuum drying time is 6-18 hours.
[0017] The foam metal substrate pretreatment method comprises the following steps: subjecting the foam metal substrate to ultrasonic treatment in a hydrochloric acid solution with a volume concentration of 10 to 30%, and then cleaning the foam metal substrate to remove surface oxides.
[0018] The pretreated foam metal substrate is immersed in a noble metal salt solution, and the self-corrosion reaction that occurs during the stirring process is as follows:
[0019] On the anode reaction side, the surface of the foam metal substrate will be oxidized to form metal ions;
[0020] On the cathode reaction side, oxygen in the air diffuses on the surface of the foam metal substrate and is reduced to OH - ; OH formed on the cathode side - The metal ions formed on the anode side combine to form metal hydroxides, which nucleate, crystallize and grow into nanosheet arrays on the surface of the foam metal substrate. The noble metal ions on the cathode side are also reduced to noble metals and attached to the surface of the metal hydroxide nanosheet arrays in the form of noble metal particles.
[0021] An application of the composite catalyst of hydroxide-loaded precious metal particles in electrochemical denitration and ammonia production reaction.
[0022] The technical solution of the present invention has the following advantages:
[0023] The present invention provides a method for preparing hydroxide-loaded precious metal particles, which adopts a self-corrosion method and synthesizes a composite structure of hydroxide-loaded precious metal particles in situ on a metal substrate through a spontaneous redox reaction. The composite catalyst of oxide-loaded precious metal particles is an integrated self-supporting electrode, which avoids the binder required in the traditional powder catalyst electrode preparation process and the cumbersome catalyst slurry configuration and coating process, while improving the structural stability of the catalyst.
[0024] The composite catalyst of oxide-loaded precious metal particles proposed in the present invention has a multilayer structure, comprising a substrate, a carrier and nanoparticles: the substrate is a foamed metal; the carrier is a metal hydroxide formed in situ by the foamed metal; and the metal hydroxide is loaded with precious metal nanoparticles. The metal hydroxide has a strong interaction with the interfacial water molecules, which can promote the activation and dissociation of the interfacial water molecules, thereby providing the required active hydrogen for electrochemical denitrification; the precious metal nanoparticles are conducive to the adsorption of nitrate ions, promoting the electrochemical reduction of nitrate ions to ammonia; there is a strong metal-carrier interaction between the metal hydroxide and the precious metal nanoparticles, which can accelerate the transmission of interfacial charges and improve the electrochemical reaction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 Schematic diagram of the preparation principle of Ni(OH)2-loaded Ru metal particle composite catalyst
[0027] Figure 2 This is a scanning electron microscope image of the nickel foam metal substrate;
[0028] Figure 3 This is a transmission electron microscope image of the Ni(OH)2-loaded Ru metal particle composite catalyst of Example 1;
[0029] Figure 4 The Faraday efficiency of electrochemical denitration and ammonia production under different voltages for the Ni(OH)2-loaded Ru metal particle composite catalyst in Example 1;
[0030] Figure 5 Energy efficiency of electrochemical denitrification and ammonia production under different voltages for different catalysts;
[0031] Figure 6The change of nitrogen content in the continuous electrolysis of nitric acid in simulated wastewater by Ni(OH)2-loaded Ru metal particle composite catalyst;
[0032] Figure 7 This is the charging and discharging working principle diagram of the hybrid flow battery;
[0033] Figure 8 This is a diagram of a long-term charge and discharge cycle of a hybrid flow battery;
[0034] Fig. 9 This is a diagram of the long-term charge and discharge cycle of the hybrid flow battery. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] A composite catalyst of hydroxide-loaded precious metal particles comprises a foam metal substrate, a metal hydroxide nanosheet array is crystallized on the surface of the foam metal substrate, and precious metal particles are attached to the surface of the metal hydroxide nanosheet array.
[0037] The foam metal substrate is foam nickel, foam cobalt or foam iron, and the metal hydroxide nanosheet arrays are respectively nickel hydroxide nanosheet arrays, cobalt hydroxide nanosheet arrays and iron hydroxide nanosheet arrays.
[0038] The precious metal particles are ruthenium, silver, palladium, gold or rhodium, and the precious metal particles come from precious metal salts of ruthenium chloride, silver nitrate, palladium chloride, gold chloride and rhodium chloride, respectively.
[0039] The present invention provides a method for preparing hydroxide-loaded noble metal particles, comprising the following steps:
[0040] The foam metal substrate was pretreated with hydrochloric acid of a certain concentration and then washed with deionized water;
[0041] A noble metal salt solution of a certain concentration is prepared, the pretreated foam metal substrate is immersed in the solution and stirred for a certain period of time, then washed with deionized water, and vacuum dried to obtain a composite catalyst of hydroxide-loaded noble metal particles.
[0042] Preferred conditions: hydrochloric acid concentration is 10-30% (volume concentration), more preferably 20%; the foam metal can be foam nickel, foam cobalt, or foam iron; the thickness of the foam metal base is preferably 0.3-2.0 mm, more preferably 1.0 mm; the pore size is preferably 0.3-0.6 mm, more preferably 0.45 mm. The present invention has no special limitation on the size of the foam metal, which can be set as needed.
[0043] The noble metal salt may be selected from ruthenium chloride, silver nitrate, palladium chloride, gold chloride, and rhodium chloride; the concentration of the noble metal salt solution is 2.5 to 10 mM, more preferably 5 mM;
[0044] The stirring speed is preferably 400-800 rpm, more preferably 600 rpm; the stirring time is preferably 10-30 minutes, more preferably 20 minutes; the vacuum drying temperature is preferably 50-70°C, more preferably 60°C; the vacuum drying time is preferably 6-18 hours, more preferably 12 hours.
[0045] The prepared hydroxide-loaded precious metal particle integrated electrode has a Faraday efficiency of nearly 100% for electrosynthesizing ammonia at an ultra-low voltage of 0V (relative to the reversible hydrogen electrode potential) in simulated industrial wastewater containing 0.1M nitrate ion concentration; at +0.1V (relative to the reversible hydrogen electrode potential), the energy efficiency reaches 44.6%; after 7 hours of continuous electrolysis, the nitrate ion removal rate in the simulated industrial wastewater reaches 95.5%, and the residual nitrate ion nitrogen content is less than 10ppm, reaching the international application water standard. The prepared hydroxide-loaded precious metal particle integrated electrode can be used in a hybrid flow battery, using a mixture of nitrate-containing wastewater and an alcohol solution as the positive electrode electrolyte, with a charge and discharge cycle life of more than 500 cycles, while realizing wastewater denitration and the synthesis of high value-added ammonium formate on the positive electrode side.
[0046] The ultrasonic treatment time is preferably 10 to 30 minutes, more preferably 20 minutes; there is no specific requirement for the ultrasonic treatment power, as long as the oxide layer on the surface of the foam metal can be removed; in the present invention, the water used for washing is preferably deionized water.
[0047] Example 1
[0048] A nickel foam metal substrate with a thickness of 1.0 mm and a pore size of 0.45 mm was cut into a size of 3 cm × 1 cm, immersed in a hydrochloric acid solution with a volume concentration of 20%, ultrasonically treated for 15 minutes, and washed with deionized water;
[0049] The pretreated nickel foam metal substrate was immersed in a 5 mM concentration of ruthenium chloride solution, stirred at 600 rpm for 20 minutes, then washed with deionized water, and vacuum dried at 60°C for 12 hours to obtain a composite catalyst of Ni(OH)2 loaded with Ru metal particles.
[0050] Comparative Example 1
[0051] The Ru metal particle material based on nickel foam was prepared according to the method of Example 1, except that saturated argon gas was introduced into the ruthenium chloride solution and oxygen was excluded.
[0052] Comparative Example 2
[0053] A Ni(OH)2 material based on nickel foam was prepared according to the method of Example 1, except that the ruthenium chloride solution was replaced with a sodium chloride solution of the same concentration.
[0054] The schematic diagram of the Ni(OH)2-loaded Ru metal particle composite catalyst prepared according to the method of the present invention is as follows: Figure 1 When nickel foam is immersed in ruthenium chloride solution, self-corrosion reaction will occur: on the anode reaction side, the surface of the foam metal Ni substrate will be oxidized to form Ni 2+ On the cathode reaction side, oxygen in the air diffuses onto the surface of the Ni foam substrate and is reduced to OH - , OH formed on the cathode side - Ni formed on the anode 2+ Combined to form Ni(OH)2, Ni(OH)2 nucleated, crystallized and grew into nanosheet arrays on the surface of the foamed Ni substrate; in addition, Ru on the cathode side 3+ It will also be reduced to metallic Ru and attached to the surface of Ni(OH)2 nanosheet array in the form of Ru metal particles. 2+ with Ru / Ru 3+ The redox potential difference can drive the self-corrosion reaction spontaneously without additional heating.
[0055] The prepared materials were characterized by scanning electron microscopy. Figure 2 (a) is a scanning electron microscope image of the nickel foam metal substrate; Figure 2 (b) is a scanning electron microscope image of the Ni(OH)2-loaded Ru metal particle composite catalyst prepared in Example 1, and the catalyst exhibits a nanosheet array morphology; Figure 2 (c) is the Ru metal particle material with nickel foam as the substrate prepared in Comparative Example 1; Figure 2 (d) is a Ni(OH)2 material based on nickel foam prepared in Example 2. The Ni(OH)2-loaded Ru metal particle composite catalyst prepared in Example 1 was characterized by transmission electron microscopy. Figure 3 As shown, the Ni(OH)2 surface is loaded with Ru metal particles with a size of 5 to 10 nm.
[0056] In simulated industrial wastewater containing 0.1M nitrate ion concentration, the electrochemical denitrification and ammonia production performance of different catalysts were tested by applying a certain external voltage. Figure 4 The Faraday efficiency of electrochemical denitration and ammonia production of the Ni(OH)2-loaded Ru metal particle composite catalyst prepared in Example 1 at different voltages is as follows. At an ultra-low voltage of 0V (relative to the reversible hydrogen electrode potential), the Faraday efficiency of electrosynthetic ammonia is close to 100%. Figure 5 It is the energy efficiency of electrochemical denitrification and ammonia production of different catalysts at different voltages. The Ni(OH)2-loaded Ru metal particle composite catalyst prepared in Example 1 has an energy efficiency of 44.6% at +0.1V (relative to the reversible hydrogen electrode potential), which is much higher than the Ru metal particle catalyst based on nickel foam prepared in Comparative Example 1 and the Ni(OH)2 catalyst based on nickel foam prepared in Comparative Example 2. Figure 6 The nitrogen content of the Ni(OH)2-loaded Ru metal particle composite catalyst prepared in Example 1 during the continuous electrolysis of nitric acid in simulated wastewater is changed. As the electrolysis time increases, the nitrate nitrogen content decreases significantly, the nitrite nitrogen content is almost 0, and the ammonia nitrogen content increases significantly. When the continuous electrolysis time reaches 7 hours, the nitrate nitrogen content is less than 10ppm, reaching the standard for nitrate nitrogen content in drinking water. The above results show that the Ni(OH)2-loaded Ru metal particle composite catalyst exhibits excellent electrochemical denitration and ammonia production performance, and has good application value in the fields of wastewater denitration and clean ammonia production.
[0057] Figure 7 This is a diagram of the charging and discharging working principle of the hybrid flow battery. The Ni(OH)2-loaded Ru metal particle self-supporting integrated electrode prepared in Example 1 is used as the positive electrode, and a certain amount of ethanol is added to the simulated industrial wastewater containing nitrate ions as the positive electrode side electrolyte; the zinc sheet is used as the negative electrode, and the alkaline solution containing zinc acetate is used as the negative electrode side electrolyte; the positive electrode side and the negative electrode side are separated by a diaphragm, and the electrolyte flows through a peristaltic pump during operation to enhance mass transfer. During the discharge process, nitrate ions are reduced to ammonia, and the metal zinc sheet is oxidized to Zn(OH)4 2- During the charging process, ethanol is oxidized to formic acid and reduced to Zn(OH)4 2- The ethanol additive can be replaced by methanol or isopropanol. On the positive electrode side, the ammonia produced during the discharge process combines with the formic acid produced during the charging process to obtain ammonium formate. Therefore, the hybrid flow battery can not only realize charging and discharging, but also convert nitrate ion pollutants into high-value-added ammonium formate. Figure 8 This is a long-term charge and discharge cycle diagram of a hybrid flow battery, with the number of cycles reaching 500 times. Fig. 9 This is the NMR spectrum of the positive electrolyte after the hybrid flow battery charge and discharge cycle, which can confirm the formation of ammonium formate products. Therefore, the Ni(OH)2-loaded Ru metal particle self-supporting integrated electrode prepared in Example 1 can not only promote clean energy conversion, but also realize wastewater denitrification and the synthesis of high value-added chemicals.
[0058] Example 2
[0059] A foamed cobalt substrate with a thickness of 1.0 mm and a pore size of 0.45 mm was cut into a size of 3 cm × 1 cm, immersed in a hydrochloric acid solution with a volume concentration of 30%, ultrasonically treated for 30 minutes, and washed with deionized water;
[0060] The pretreated cobalt foam substrate was immersed in a 2.5 mM concentration of silver nitrate solution, stirred at 400 rpm for 30 minutes, then washed with deionized water, and vacuum dried at 70° C. for 18 hours to obtain a composite catalyst of cobalt hydroxide loaded silver metal particles.
[0061] Example 3
[0062] A foamed iron substrate with a thickness of 1.0 mm and a pore size of 0.45 mm was cut into a size of 3 cm × 1 cm, immersed in a hydrochloric acid solution with a volume concentration of 10%, ultrasonically treated for 10 minutes, and washed with deionized water;
[0063] The pretreated foamed iron substrate was immersed in a 10 mM concentration of palladium chloride solution, stirred at 800 rpm for 10 minutes, then washed with deionized water, and vacuum dried at 50° C. for 6 hours to obtain a composite catalyst of iron hydroxide-loaded palladium metal particles.
[0064] Example 4
[0065] A foamed cobalt substrate with a thickness of 1.0 mm and a pore size of 0.45 mm was cut into a size of 3 cm × 1 cm, immersed in a hydrochloric acid solution with a volume concentration of 10%, ultrasonically treated for 10 minutes, and washed with deionized water;
[0066] The pretreated cobalt foam substrate was immersed in a 10 mM gold chloride solution, stirred at 800 rpm for 10 minutes, then washed with deionized water, and vacuum dried at 50° C. for 6 hours to obtain a composite catalyst of cobalt hydroxide loaded with gold metal particles.
[0067] Example 5
[0068] A nickel foam substrate with a thickness of 1.0 mm and a pore size of 0.45 mm was cut into a size of 3 cm × 1 cm, immersed in a hydrochloric acid solution with a volume concentration of 10%, ultrasonically treated for 10 minutes, and washed with deionized water;
[0069] The pretreated nickel foam substrate was immersed in a 10 mM rhodium chloride solution, stirred at 800 rpm for 10 minutes, then washed with deionized water, and vacuum dried at 50° C. for 6 hours to obtain a composite catalyst of nickel hydroxide loaded rhodium metal particles.
[0070] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A composite catalyst of hydroxide-supported noble metal particles, characterized in that: The composite catalyst comprises a foam metal substrate, a metal hydroxide nanosheet array is crystallized on the surface of the foam metal substrate, and noble metal particles are attached to the surface of the metal hydroxide nanosheet array.
2. The composite catalyst of hydroxide-supported noble metal particles according to claim 1, characterized in that: The foam metal substrate is foam nickel, foam cobalt or foam iron, and the metal hydroxide nanosheet arrays are respectively nickel hydroxide nanosheet arrays, cobalt hydroxide nanosheet arrays and iron hydroxide nanosheet arrays.
3. The composite catalyst of hydroxide-supported noble metal particles according to claim 1, characterized in that: The noble metal particles are ruthenium, silver, palladium, gold or rhodium, and the size of the noble metal particles is 5-10 nm.
4. A method for preparing the composite catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: The pretreated foam metal substrate is immersed in a noble metal salt solution, stirred for 10 to 30 minutes, cleaned, and vacuum dried to obtain a composite catalyst of hydroxide-loaded noble metal particles.
5. The preparation method according to claim 3, characterized in that: The foam metal is selected from foam nickel, foam cobalt or foam iron.
6. The preparation method according to claim 3, characterized in that: The noble metal salt is one of ruthenium chloride, silver nitrate, palladium chloride, gold chloride or rhodium chloride, and the concentration of the noble metal salt solution is 2.5-10 mM.
7. The preparation method according to claim 3, characterized in that: The stirring speed is 400-800 rpm, the vacuum drying temperature is 50-70° C., and the vacuum drying time is 6-18 hours.
8. The preparation method according to claim 3, characterized in that: The foam metal substrate pretreatment method comprises the following steps: subjecting the foam metal substrate to ultrasonic treatment in a hydrochloric acid solution with a volume concentration of 10 to 30%, and then cleaning the foam metal substrate to remove surface oxides.
9. The preparation method according to claim 3, characterized in that: The pretreated foam metal substrate is immersed in a noble metal salt solution, and the self-corrosion reaction that occurs during the stirring process is as follows: On the anode reaction side, the surface of the foam metal substrate will be oxidized to form metal ions; On the cathode reaction side, oxygen in the air diffuses on the surface of the foam metal substrate and is reduced to OH - ; The OH- formed on the cathode side combines with the metal ions formed on the anode side to form metal hydroxides, and at the same time, the metal hydroxides nucleate, crystallize and grow into nanosheet arrays on the surface of the foam metal substrate; the noble metal ions on the cathode side are also reduced to noble metals and attached to the surface of the metal hydroxide nanosheet arrays in the form of noble metal particles.
10. Use of the composite catalyst of hydroxide-supported precious metal particles according to claim 1 in an electrochemical denitrification and ammonia production reaction.